109Cd K x ray fluorescence measurements of tibial lead content in young adults exposed to lead in early childhood. Issue 7 (1st July 2000) - McNeill, Fiona E; Stokes, Lynette; Brito, José A A; Chettle, David R; Kaye, Wendy E
Abstract : OBJECTIVES: Tibia lead measurements were performed in a population of 19–29 year old people who had been highly exposed to lead in childhood to find whether lead had persisted in the bone matrix until adulthood. METHODS: 109 Cd K x ray fluorescence was used to measure the tibia lead concentrations of 262 exposed subjects and 268 age and sex matched controls. Questionnaire data allowed a years of residence index to be calculated for exposed subjects. A cumulative blood lead index was calculated from the time weighted integration of available data of blood lead. RESULTS: The mean (SEM) difference between exposed and control men was 4.51 (0.35) μg Pb/g bone mineral, and between exposed and control women was 3.94 (0.61) μg Pb/g bone mineral. Grouped mean bone lead concentrations of exposed subjects were predicted best by age. When exposed and control subjects' data were combined, grouped mean bone lead concentrations were predicted best by cumulative blood lead index. The years of residence index was neither a good predictor of bone lead concentrations for exposed subjects nor for exposed and control subjects combined. Finally, exposed subjects had increased current blood lead concentrations that correlated significantly with bone lead values. CONCLUSION: Bone lead concentrations of exposed subjects were significantly increased compared with those of control subjects. Lead from exposure in early childhood had persisted in the bone matrix until adulthood. Exposed subjects had increased blood lead concentrations compared with controls. Some of this exposure could be related to ongoing exposure. However, some of the increase in blood lead concentration in adult exposed subjects seemed to be a result of endogenous exposure from increased bone lead stores. The endogenous exposure relation found for men was consistent with reported data, but the relation found for women was significantly lower. Further research is needed to find whether the observed differences are due to sex, or pregnancy and lactation.